Implications of Generalized Z-Z' Mixing - Babu, K; Kolda, C; March-Russell, J (1997)
We discuss experimental implications of extending the gauge structure of the Standard Model to include an additional U(1) interaction broken at or near the weak scale. We work with the most general, renormalizable Lagrangian for the SU(2)× U(1)× U(1) sector, with emphasis on the phenomenon of gauge kinetic mixing between the two U(1) gauge fields, and do not restrict ourselves to any of the "canonical" Z' models often discussed in the literature. Low-energy processes and Z-pole precision measurements are specifically addressed.